Exploring the Relationship between Generational Diversity, Employee Engagement, and Turnover Intention: Evidence from Manufacturing Workers - Karyati, Siti; Suwandi, Suwandi (Lentera Ilmu Nusantara, 2025)
Generational diversity is a challenge as well as an opportunity to increase employee engagement, which can affect turnover intention. This study analyzes the influence of these two factors on manufacturing companies in Cikarang. With a quantitative approach, this study uses a purposive sampling method with a total of 73 respondents. Data was collected through questionnaires and analyzed using the Structural Equation Modeling technique based on Partial Least Squares (PLS). The results show that both generational diversity and employee engagement have a negative influence on turnover intention, but the influence is not significant. These findings indicate that while generational diversity can create unique work dynamics and employee engagement increases employee emotional engagement, these factors are not the main determinants of turnover intention in the manufacturing sector. Job stability, compensation, and a structured work culture play a greater role in influencing employees' intentions to stay in the company. This study provides important insights for management to develop human resource management strategies that focus on strengthening job stability, providing competitive incentives, and creating a cross-generational inclusive work environment. The novelty of this study lies in its focus on the manufacturing industry context in Cikarang, where generational diversity is high yet rarely studied in relation to turnover intention. By integrating generational differences and employee engagement in a single empirical model, this research offers a new perspective that can guide more targeted HR interventions in multi-generational workplace settings.